Cinema and nation - Hjort, Mette; MacKenzie, Scott, 1967- (London ; New York : Routledge, 2000)
Cinema and Nation considers the ways in which film production and reception are shaped by ideas of national belonging and examines the implications of globalisation for the concept of national cinema.
The sociological scope of 'national cinema' / Philip Schlesinger -- Frank Capra meets John Doe : anti-politics in American national identity / Charles Lindholm, John A. Hall -- Images of the nation : cinema, art and national identity / Anthony Smith -- The limiting imagination of national cinema / Andrew Higson -- National cinema : a theoretical assessment / Ian Jarvie -- Framing national cinemas / Susan Hayward -- Themes of nation / Mette Hjort -- Cinematic nation-building : Eisenstein's The old and the new / Noël Carroll, Sally Banes -- The nation vanishes : European co-productions and popular genre formulae in the 1950s and 1960s / Tim Bergfelder -- The new Scottish cinema / Duncan Petrie -- Indonesia : the movie / Martin Roberts -- Notes on Polish cinema, nationalism and Wajda's Holy week / Paul Coates -- Deep nation : the national question and Turkish cinema culture / Kevin Robins, Asu Aksoy -- Fragmenting the nation : images of terrorism in Indian popular cinema / Sumita S. Chakravarty -- Mimetic nationhood : ethnography and the national / Scott MacKenzie -- From new German cinema to the post-wall cinema of consensus / Eric Rentschler -- Contemporary cinema : between cultural globalisation and national interpretation / Ulf Hedetoft -- Birthing nations / Jane M. Gaines.
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: National characteristics in motion pictures; Motion picture industry -- Government policy; Motion pictures -- Political aspects; Caractéristiques nationales au cinéma.; Cinéma -- Industrie -- Politique gouvernementale; Cinéma -- Aspect politique; PERFORMING ARTS -- Film & Video -- Reference; Motion picture industry -- Government policy; Motion pictures -- Political aspects; National characteristics in motion pictures; Nation; Film; National characteristics in motion pictures; Motion picture industry -- Government policy; Motion pictures -- Political aspects; Theatre, Film and Television Studies; Electronic books; Aufsatzsammlung